Research on Educational Games in Learning in Indonesia: A Systematic Review of the Literatures - Ali Usman; Agus Prasetyo Utomo; Fitri Amilia; Dzarna Dzarna; Chusnul Khotimah Galatea (Jurnal Penelitian Pendidikan IPA, 2024)
Research on educational games in learning contexts and advances in science and technology are becoming increasingly important. This research aims to analyze the use of educational games in the learning context in Indonesia, focusing on computer science and social science. The method used in this research is a Systematic Literature Review (SLR), with inclusion criteria of publication period between 2018 and 2023, English language articles, article accessibility, and relevance to computer science and social sciences. The results of this research analysis include several important findings, namely: 1) the number of educational game document publications has fluctuated, 2) affiliation trends vary, 3) author trends also vary, and 4) the results of the systematic analysis show that educational games can improve student academic achievement, problem-solving abilities, creative thinking, and independent learning abilities. In addition, the role of teachers and parents is recognized as an important factor in supporting and maximizing the benefits of digital educational technology. The findings from this research emphasize the importance of designing learning that integrates educational game-based approaches to improve the quality of learning and achieve better learning outcomes for students. The implications of this research provide a basis for developing innovative and sustainable learning strategies in the fields of computer science and social sciences in Indonesia